Highly Accessible Atomically Dispersed Fe‐Nx Sites Electrocatalyst for Proton‐Exchange Membrane Fuel Cell. Issue 5 (29th January 2021) - Guo, Jianing; Li, Bingjie; Zhang, Qiyu; Liu, Qingtao; Wang, Zelin; Zhao, Yufei; Shui, Jianglan; Xiang, Zhonghua
Abstract: Atomically dispersed transition metal‐N x sites have emerged as a frontier for electrocatalysis because of the maximized atom utilization. However, there is still the problem that the reactant is difficult to reach active sites inside the catalytic layer in the practical proton exchange membrane fuel cell (PEMFC) testing, resulting in the ineffective utilization of the deeply hided active sites. In the device manner, the favorite structure of electrocatalysts for good mass transfer is vital for PEMFC. Herein, a facile one‐step approach to synthesize atomically dispersed Fe‐N x species on hierarchically porous carbon nanostructures as a high‐efficient and stable atomically dispersed catalyst for oxygen reduction in acidic media is reported, which is achieved by a predesigned hierarchical covalent organic polymer (COP) with iron anchored. COP materials with well‐defined building blocks can stabilize the dopants and provide efficient mass transport. The appropriate hierarchical pore structure is proved to facilitate the mass transport of reactants to the active sites, ensuring the utilization of active sites in devices. Particularly, the structurally optimized HSAC/Fe‐3 displays a maximum power density of up to 824 mW cm −2, higher than other samples with fewer mesopores. Accordingly, this work will offer inspirations for designing efficient atomically dispersed electrocatalyst in PEMFC device. Abstract : A facile one‐step approach to synthesize atomically dispersed Fe‐N x species on hierarchically porous carbon nanostructures is reported, which facilitates the mass transport of reactants and electrolytes to the active sites, thus ensuring the efficient utilization of active sites in practical PEMFC devices.